IL-21 is associated with natural resistance to HIV-1 infection in a Colombian HIV exposed seronegative cohort (2020)
ABSTRACT: Higher IL-21 levels were associated with natural resistance to HIV infection in an Italian cohort. Thus we wanted to confirm such association in HIV exposed seronegative individuals (HESN) from Colombia. Cells from HESN were less susceptible to infection and expressed higher IL-21 mRNA levels than healthy controls at both baseline and 7-days post-infection; similar results were observed for IL-6, perforin, and granzyme. These results suggest that IL-21/IL-6 increase may be a distinctive quality in the profile of HIV 1 resistance, at least during sexual exposure. However, further studies are necessary to confirm the specific protective mechanisms of these cytokines.